Analisis Kinerja Perusahaan Berdasarkan Good Corporate Governance pada Bank Umum Syariah di Indonesia - Masruroh, Aniswatun; Yazid, Muhammad; Feriansyah, Ardian (Jurnal Maps (Manajemen Perbankan Syariah), 2024)
The impact of the development of Islamic banks is the emergence of challenges in efforts to improve the company's image in the eyes of customers and investors. Efforts to improve the image of companies, especially Sharia banks, can be made by maximizing good corporate governance. This research aims to analyze company performance based on good corporate governance in Islamic commercial banks for the 2018-2022 period. The research method used is descriptive qualitative with secondary data obtained from the annual financial reports of each Islamic bank. Data analysis uses Eviews 12 output. The results of this research show that 8 of the 14 Sharia Commercial Banks in Indonesia have met the GCG assessment criteria in accordance with applicable laws and regulations. However, there is one assessment, namely that the results of the analysis of the Sharia Supervisory Board meetings are not in accordance with PBI regulation No.11/3/PBI/2009 which states that the Sharia Supervisory Board (DPS) has an obligation to hold 12 meetings. The company that does not meet these criteria is Bank Victoria Syariah in 2022.